2019
DOI: 10.3390/ijerph16071278
|View full text |Cite
|
Sign up to set email alerts
|

Family Functioning and Psychological Health of Children with Mentally Ill Parents

Abstract: Parental mental illness can be linked to reduced family functioning, which is associated with more conflicts, less adaptability and cohesion as well as a disorganized pattern of everyday planning. Concurrently, family functioning is an important moderator for the influence of parental mental disorders on the development of the children. Consequently, the current study addresses the correlation of family functioning in families with mentally ill parents and the psychological health of the children. The sample c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 46 publications
5
31
0
7
Order By: Relevance
“…Caregiving skills were not measured in this trial but we found a significant effect upon family functioning, indicating that an increased level of functioning is related to a higher probability of using any type of health or social service and of incurring costs in the first part of the model. Family functioning is known to be correlated with the mental health of COPMI [ 42 ], which is also true for our sample (r = 0.344, p < 0.001), indicating a good resilience in participating children. Further investigations about resilience in COPMI and the influence of individual and family functioning on costs are needed.…”
Section: Discussionsupporting
confidence: 72%
“…Caregiving skills were not measured in this trial but we found a significant effect upon family functioning, indicating that an increased level of functioning is related to a higher probability of using any type of health or social service and of incurring costs in the first part of the model. Family functioning is known to be correlated with the mental health of COPMI [ 42 ], which is also true for our sample (r = 0.344, p < 0.001), indicating a good resilience in participating children. Further investigations about resilience in COPMI and the influence of individual and family functioning on costs are needed.…”
Section: Discussionsupporting
confidence: 72%
“…Opposite these risk factors, specific protective factors have been identified. These are e.g., primarily positive relationships inside and outside the family, information about the parental disease which is adequate for the children's age and development, adequate individual and familial coping strategies, and supporting parental and family dynamics ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when subjects enjoy a good mood and good emotional health, relationships with their parents and peer groups will be more fruitful. In some research it has been found that dysfunctionalities in social and family relationships greatly affect individuals, causing various behavioral and emotional problems [37][38][39].…”
Section: Discussionmentioning
confidence: 99%